Avaliação do desempenho térmico em edificações de blocos estruturais cerâmicos e de blocos estruturais de concreto para a zona bioclimática 2 brasileira - Kappaun, Kamila (2012)
Structural masonry has been used more and more in Brazil, but this technology has limitations on research which report its thermal behavior. In Rio Grande do Sul, the clay structural block is the most widely used, while in Brazil as a whole, concrete structural blocks are more popular. Thermally speaking, it is not known which block is better suited for the Brazilian bioclimatic zone 2. The thermal performance of two structures built with structural masonry, one with clay and one with concrete, is analyzed in this thesis. Initially, the values for the thermal characteristics of both types of closure were defined, to contrast the differences among them, with the intent to thermally analyze both buildings. The thermal transmittance, the thermal capacity, and the thermal delay were calculated. In loco measurements were made in buildings with the same floor plan, solar orientation, and implementation, but which were built with different structural blocks. The analyses contemplated different parameters which could have influenced the results, such as the influence of the ceiling and solar orientation. The results from both buildings were compared with the measured external temperatures, and also analyzed with regards to the observance of a standardized thermal performance.